If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33 = (3x + -8)(7x + 4) Reorder the terms: 33 = (-8 + 3x)(7x + 4) Reorder the terms: 33 = (-8 + 3x)(4 + 7x) Multiply (-8 + 3x) * (4 + 7x) 33 = (-8(4 + 7x) + 3x * (4 + 7x)) 33 = ((4 * -8 + 7x * -8) + 3x * (4 + 7x)) 33 = ((-32 + -56x) + 3x * (4 + 7x)) 33 = (-32 + -56x + (4 * 3x + 7x * 3x)) 33 = (-32 + -56x + (12x + 21x2)) Combine like terms: -56x + 12x = -44x 33 = (-32 + -44x + 21x2) Solving 33 = -32 + -44x + 21x2 Solving for variable 'x'. Combine like terms: 33 + 32 = 65 65 + 44x + -21x2 = -32 + -44x + 21x2 + 32 + 44x + -21x2 Reorder the terms: 65 + 44x + -21x2 = -32 + 32 + -44x + 44x + 21x2 + -21x2 Combine like terms: -32 + 32 = 0 65 + 44x + -21x2 = 0 + -44x + 44x + 21x2 + -21x2 65 + 44x + -21x2 = -44x + 44x + 21x2 + -21x2 Combine like terms: -44x + 44x = 0 65 + 44x + -21x2 = 0 + 21x2 + -21x2 65 + 44x + -21x2 = 21x2 + -21x2 Combine like terms: 21x2 + -21x2 = 0 65 + 44x + -21x2 = 0 Factor a trinomial. (65 + -21x)(1 + x) = 0Subproblem 1
Set the factor '(65 + -21x)' equal to zero and attempt to solve: Simplifying 65 + -21x = 0 Solving 65 + -21x = 0 Move all terms containing x to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + -21x = 0 + -65 Combine like terms: 65 + -65 = 0 0 + -21x = 0 + -65 -21x = 0 + -65 Combine like terms: 0 + -65 = -65 -21x = -65 Divide each side by '-21'. x = 3.095238095 Simplifying x = 3.095238095Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {3.095238095, -1}
| 7(p+7q-13)= | | N^2-13n+40=0 | | 5(6y+12)=6(12y-4) | | 30=-1.2v | | 2x^2+10x-18=0 | | 5(6y+12)=6(12-4) | | -2(4n+4)=2 | | 15x^4-12x^3+3x^2=0 | | y-(-3)=2(x-2) | | (-1)x^3=27 | | 6x+2.72=4.22 | | (1+z)(5z-2)=0 | | 10x+26(x-2)=128 | | 5x+27(x-4)=84 | | 3m+38=9m-4 | | 5m+14=9m-2 | | -6z+2(5-3z)=8(-3z+2)+10 | | 4(p+8q-13)= | | 22-2=6n | | -3k=14-k | | 6y-8(-3)=24 | | 6y-8x=24 | | 5(x+3)=3(7x+3)-2 | | g(x+5)=x^2+2x+3 | | 4x^2+8-77=00 | | 6x+21=2x-1 | | g(-1)=x^2+2x+3 | | g(x)=x^2+2x+3 | | 4(8c)=3 | | 3p=8 | | a-2=7+10 | | 3x+5=-34 |